Innovative Food System Risk Management of The Baduy Tribe - Asep Taryana; Fitri Kinasih Husnul Khotimah; Noer Azam Achsani; Bustanul Arifin (School of Business, IPB University (SB-IPB), 2020)
This study aimed to identify and analyze the food system risk management of the Baduy Tribe and its managerial implications for food security. The scope of this study was limited to the huma rice food system. The research method utilized was the ethnographic study to obtain primary data. The data were analyzed using the ISO 31000 risk management process approach. Based on this study’s results, the creative and innovative determination in Baduy Tribe did not lead to the modernization of technology but referred to a facilitated way of life in achieving goals. The risks associated with the development of science and technology, as well as its dependence on nature, were in the high category for the Baduy’s indigenous ban (pikukuh) did not accept the use of technology and formal education. The risks associated with food availability and post-harvest food access were in the low category due to the risk management process implemented by the Baduy Tribe hereditarily through the leuit storage system. The findings on an innovative food system risk management of the Baduy Tribe is expected to provide a managerial perspective on the food system to achieve national food security. Keywords: Baduy Tribe, ethnographic study, food security, food system, risk management